Cocaine Differentially Modulates Chemokine Production by Mononuclear Cells from Normal Donors and Human Immunodeficiency Virus Type 1-Infected Patients - Nair, Madhavan P. N. (American Society for Microbiology, 2000)
Earlier studies have supported a significant role for cocaine in the susceptibility to and the progression of human immunodeficiency virus type 1 (HIV-1) infection. Recently, several unique HIV-1 entry coreceptors (e.g., CCR5 and CCR3) and a trio of HIV-1-specific suppressor chemokines, namely, RANTES (regulated-upon-activation T expressed and secreted), macrophage inflammatory protein 1α (MIP-1α) and MIP-1β, were identified. Although cocaine has been linked to the immunopathogenesis of HIV-1 infection, the corresponding cellular and molecular mechanism(s) have not been well defined. We hypothesize that cocaine mediates these pathologic effects through the downregulation of HIV-1-suppressing chemokines and/or upregulating HIV-1 entry coreceptors in HIV-1-infected subjects, resulting in disease progression to AIDS. Our results show that cocaine selectively downregulates endogenous MIP-1β secretion by normal peripheral blood mononuclear cells (PBMC), while cocaine did not affect the MIP-1β production by PBMC from AIDS patients. Cocaine also selectively suppresses lipopolysaccharide-induced MIP-1β production by PBMC from HIV-infected patients. Further, cocaine significantly downregulates endogenous MIP-1β gene expression, while it upregulates HIV-1 entry coreceptor CCR5 by normal PBMC. These studies suggests a role for cocaine as a cofactor in the pathogenesis of HIV infection and support the premise that cocaine increases susceptibility to and progression of HIV-1 infection by inhibiting the synthesis of HIV-1 protective chemokines and/or upregulating the HIV-1 entry coreceptor, CCR5.